2023
DOI: 10.1080/17439760.2023.2178955
|View full text |Cite
|
Sign up to set email alerts
|

Can repeated and reflective prosocial experiences in sport increase generosity in adolescent athletes?

Abstract: In partnership with a sport-based Experiential Philanthropy Intervention (EPI)-The Play Better Program-we conducted a pre-registered, longitudinal experiment examining whether repeatedly reflecting on prosocial activity could boost adolescents' objective generosity. Adolescents (N=114; aged 9-16) practiced charitable giving throughout their 2month sports season and were randomly assigned to repeatedly reflect on the importance of their prosocial activity (Reflection condition) or to write about their everyday … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…As studies with young adolescents suggest, the ability to be mindful and compassionate towards others and oneself may not always be mutually reinforcing (Bayır-Toper et al, 2022). Youth development programs need to address and promote the growth of authenticity, or the ability to become emotionally mature (Proulx et al, 2023). Given that our present findings showed that in addition to psychological traits, the physical self-concept played a role in adolescents' self-definitions, programs for youth need to draw on a humanist and relational approach to development.…”
Section: Discussionmentioning
confidence: 99%
“…As studies with young adolescents suggest, the ability to be mindful and compassionate towards others and oneself may not always be mutually reinforcing (Bayır-Toper et al, 2022). Youth development programs need to address and promote the growth of authenticity, or the ability to become emotionally mature (Proulx et al, 2023). Given that our present findings showed that in addition to psychological traits, the physical self-concept played a role in adolescents' self-definitions, programs for youth need to draw on a humanist and relational approach to development.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the link between prosociality and well-being in community and schoolbased settings is critical in light of the various school-and community-based interventions that aim to nurture a prosocial identity in children, often with the expectation that these programs will enhance children's psychological well-being [29][30][31][32][33]. A wide range of children-focused, school-based prosociality programs have been developed, such as Social Emotional Learning programs, e.g., [32], Intergenerational programs (e.g., [34]), Service Learning and Community Engagement programs (e.g., [35]), Experiential Philanthropy programs (e.g., [36,37], Prosocial Mentorship programs (e.g., [38]), Character Education programs (e.g., [39]), and Moral Learning programs (e.g., [40]). All prosociality-focused interventions rest on the assumption that school-aged children can develop greater prosocial tendencies by learning about or practicing prosocial behavior in some form or another and that these experiences can foster greater well-being.…”
Section: Prosociality and Well-beingmentioning
confidence: 99%